Perancangan Sistem Basis Data Offline Dokumen Akreditasi Program Studi - Intan Mardiono; Raizummi Fil’aini; Fatin Saffanah Didin (OPSI, 2019)
Accreditation is a government assessment for a Higher Education. Based on the regulation of the minister of education and culture of the Republic of Indonesia number 87 of 2014 article 6, the validity period of the accreditation status and ranking of accredited study programs and tertiary institutions is 5 (five) years. During this time, the institution must prepare the documents used for accreditation. In 2019, the government has implemented changes to the standard accreditation assessment criteria of an institution, the evaluation of accreditation documents refers to several documents, one of them is Study Program Performance Sheet (LKPS) which is recapitulated in an excel. This research focuses on data integration at LKPS. In the LKPS excel data there is a relationship between the data with one another. One of the data that has a relationship is data related to lecturers with tridharma activities. Given that the application of this new rule began in 2019, this research focuses on designing the concept offline, namely Database integration made using Microsoft Access. LKPS analysis results have determined that there are 30 tables of which there are 22 integrated tables and 8 tables that do not have integration.